2017
DOI: 10.1186/s12917-017-1221-2
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii and Neospora caninum in farm-reared ostriches (Struthio camelus) in China

Abstract: BackgroundThe parasites Toxoplasma gondii (T. gondii) and Neospora caninum (N. caninum) are globally distributed; they infect warm-blooded animals, including many avian species. The aim of this study was to evaluate the presence of these parasites in ostriches from central China. In total, 402 ostrich (Struthio camelus) samples (293 hearts, 77 brains, and 32 serum) from slaughterhouses of the Henan Province and Hebei Province were collected. The heart juice (n = 283) and serum samples (n = 32) were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Parasitic disease is a disease that seriously endangers the development of the camel industry ( 18 , 20 , 22 , 24 ) and that not only impedes the growth and development of camels ( 14 , 17 , 19 ), but is also one of the important reasons for the peak in camel deaths in the spring, resulting in great economic losses ( 15 , 16 , 21 ). What is more, many zoonotic parasites ( 1 , 9 , 10 , 12 , 13 , 28 ) could contaminate camel milk ( 18 ) and meat, posing potential threats to food safety and the health of the majority of herders ( 9 , 21 , 22 ). The documents on camel parasitic diseases in Iran showed that 48 helminth species were detected in the digestive system ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic disease is a disease that seriously endangers the development of the camel industry ( 18 , 20 , 22 , 24 ) and that not only impedes the growth and development of camels ( 14 , 17 , 19 ), but is also one of the important reasons for the peak in camel deaths in the spring, resulting in great economic losses ( 15 , 16 , 21 ). What is more, many zoonotic parasites ( 1 , 9 , 10 , 12 , 13 , 28 ) could contaminate camel milk ( 18 ) and meat, posing potential threats to food safety and the health of the majority of herders ( 9 , 21 , 22 ). The documents on camel parasitic diseases in Iran showed that 48 helminth species were detected in the digestive system ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the seroprevalence of T. gondii in cattle was 1.93% (102/5292), which is lower than the rest of the world and China’s average infection rate. It is also lower than the seroprevalence of T. gondii in free-range chickens (18.86%, 132/700) [ 19 ], ostrich (10.20%, 20/197) [ 20 ], sheep (29.33%, 83/283) [ 21 ], swine (13.08%, 304/2325) [ 22 ], domestic cats (50%, 21/42) [ 23 ], and large cats (88.9%, 8/9) [ 24 ] in Henan Province. The maximum titer against T. gondii antibodies in dairy cattle was 3200 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 9.94% of the examined swine samples were found to be seropositive for T. gondii infection, which is lower than that of the rest of the world as well as China's average infection rate. It is also lower than the seroprevalence of T. gondii in free-range chickens, ostriches, sheep, swine, domestic cats, and large cats in Henan Province [10][11][12][13][14][15]. The reasons for the differences were as follows: the samples in this study were collected from healthy swine in slaughterhouses, improved management and intensive swine farming was developed in China recently.…”
Section: Resultsmentioning
confidence: 99%